2016
DOI: 10.1002/hbm.23410
|View full text |Cite
|
Sign up to set email alerts
|

Individual prediction of long-term outcome in adolescents at ultra-high risk for psychosis: Applying machine learning techniques to brain imaging data

Abstract: An important focus of studies of individuals at ultra-high risk (UHR) for psychosis has been to identify biomarkers to predict which individuals will transition to psychosis. However, the majority of individuals will prove to be resilient and go on to experience remission of their symptoms and function well. The aim of this study was to investigate the possibility of using structural MRI measures collected in UHR adolescents at baseline to quantitatively predict their long-term clinical outcome and level of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 40 publications
(48 reference statements)
0
44
0
Order By: Relevance
“…A total of 19 ML studies (73%) employed a support vector machine algorithm (10,30,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53), while the rest used Gaussian process (11) or convex hull classification (54), randomized trees (55), greedy algorithm (20), random forest (5), or LASSO regression (56,57). All ML models were computed with CV, whereas studies using Cox regression applied bootstrapping (28,(58)(59)(60)(61)(62), reported apparent results (i.e., the model is tested in the same sample from which it was derived) (63-68), or lacked a validation procedure.…”
Section: Effect Of Algorithm Choicementioning
confidence: 99%
See 2 more Smart Citations
“…A total of 19 ML studies (73%) employed a support vector machine algorithm (10,30,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53), while the rest used Gaussian process (11) or convex hull classification (54), randomized trees (55), greedy algorithm (20), random forest (5), or LASSO regression (56,57). All ML models were computed with CV, whereas studies using Cox regression applied bootstrapping (28,(58)(59)(60)(61)(62), reported apparent results (i.e., the model is tested in the same sample from which it was derived) (63-68), or lacked a validation procedure.…”
Section: Effect Of Algorithm Choicementioning
confidence: 99%
“…One model was built on P300 amplitude from event-related potentials and sociopersonal adjustment (62). Functional outcomes were predicted with neuroanatomical (63,9,19) and blood-based biomarkers (11), and 2 studies combined clinical and MRI measures (10,30). There were no effects of data modality on SE (p = .172) or false positive rate (p = .606) ( Table S2).…”
Section: Effect Of Data Modalitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, given that ARMS subjects are liable to develop poor functioning [178][179][180][181] and impaired quality of life 182,183 regardless of later psychosis onset, long-term functional disability, but not only psychosis onset itself, is an important target for prevention. 184 Interestingly, recent neuroimaging studies suggest that volume reduction predominantly in the fronto-limbic and subcortical regions, [184][185][186][187] cortical surface patterns, 188 progressive reduction in the white matter integrity of the corpus callosum, 189 and prefrontostriatal hyperactivation 190 may be possible neurobiological predictors of long-term functional outcome. However, because of the relatively small sample size and/or lack of treatment information during the follow-up period, these findings need replication and validation in a larger, wellcontrolled high-risk cohort.…”
Section: Early Interventionmentioning
confidence: 99%
“…For example, while multivariate signatures based on symptomatology were used in studies predicting outcome for first-episode psychosis [64] and symptom severity and persistence in post-traumatic stress disorder (PTSD) [65], only univariate and dichotomised outcomes were addressed and categorical diagnosis was presumed. When neuroimaging data were used as the signature, machine learning classifiers were used to predict categorical diagnosis [66], transition from an at-risk state to a dichotomised ‘psychosis versus health’ outcome [67] and dichotomised clozapine response [68, 69], or univariate aggregate predicted univariate global assessment of function (GAF) [70]. Only one study [71] used machine learning to predict multiple outcomes in major depressive disorder although again, these were dichotomised and did not model trajectories as multidimensional constructs.…”
Section: Step One: Multidimensional Definition Of Disordermentioning
confidence: 99%